2019
DOI: 10.1002/ccd.28627
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in coronary artery lesions and in‐hospital outcomes for patients with ST‐segment elevation myocardial infarction under the age of 45

Abstract: Objective: We aimed to compare baseline characteristics, coronary angiogram findings, and in-hospital outcomes between female and male patients with ST-segment elevation myocardial infarction (STEMI) under the age of 45 years. Background: Although sex differences in risk factor profile have been documented for young patients with STEMI, limited data exist on the prevalence of spontaneous coronary artery dissection in these patients. Methods: As part of an ongoing hospital-based registry of suspected STEMI, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 39 publications
2
21
1
15
Order By: Relevance
“…In the largest series of SCAD patients presenting with STEMI, the prevalence of SCAD in women less than 50 years old was 19%. 3 In this issue of Catherization and Cardiovascular Interventions, Vautrin et al 4 The most striking finding was that among these young patients presenting with STEMI, the prevalence of SCAD was significantly higher in women compared to men (22 vs. 3%) consistent with other studies. Among women the majority of SCAD cases were Type 2 SCAD and the left anterior descending artery was the most affected vessel consistent with prior studies.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In the largest series of SCAD patients presenting with STEMI, the prevalence of SCAD in women less than 50 years old was 19%. 3 In this issue of Catherization and Cardiovascular Interventions, Vautrin et al 4 The most striking finding was that among these young patients presenting with STEMI, the prevalence of SCAD was significantly higher in women compared to men (22 vs. 3%) consistent with other studies. Among women the majority of SCAD cases were Type 2 SCAD and the left anterior descending artery was the most affected vessel consistent with prior studies.…”
supporting
confidence: 67%
“…In this issue of Catherization and Cardiovascular Interventions , Vautrin et al 4 examined the differences in women versus men presenting with STEMI under the age of 45 among 489 patients (including 57 women, 11.6% of the total) who presented at two percutanous coronary intervention (PCI) centers in Northern France. A total of 51 women and 93 men matched 1:2 by age, year of admission, and catherization lab were included in the analysis.…”
mentioning
confidence: 99%
“…SCAD is known to be an underdiagnosed and important cause of MI especially in young women [ 36 ]. An interesting study with a small cohort found that SCAD accounted for 22% of women with STEMI under the age of 45 [ 37 ]. In general, and as performed in our cohort (86%), conservative management is preferred to revascularization [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the greatest reason for this discrepancy may be due to the different age limit of the patients included in the study and the inclusion of both STEMI and NSTEMI patient groups in most studies. 14,[18][19][20][21][22] Given the symptoms, the most common complaint of patients (95.5%) was typical chest pain. Although; typical chest pain was not statistically significant, it tended to be more common in men, while shortness of breath was significantly higher in women.…”
Section: Discussionmentioning
confidence: 99%